Evaluation of the spreading of isolated bacterias from Dental Consulting-Room using RAPD technique - Rodrigues, Marcus V.P.; Fusco-Almeida, Ana M.; Nogueira, Natália G.P.; Bertoni, Bianca W.; Torres, Simone C.Z.; Pietro, Rosemeire C.L.R. [UNESP] (My University, 2008)
The aim of this study was to investigate the spreading of isolates recovered in dental office environment using Random Amplified Polymorphic DNA technique (RAPD). The bacteria isolated and identificated from the surfaces of different dental consulting-room and staff were obtained in two moments (47 isolates total). For Klebsiella sp, Staphylococcus aureus and Escherichia coli isolates, groups with high coefficient of similarity (Sab) were obtained. Proteus vulgaris and Hafnia alvei showed lower Sab, showing however greater relationships between individual species. It was possible to determine that the majority of the isolates of individual species were closely related.
Keywords: Bacterial dissemination; Dental consulting-room; RAPD